Creating inclusive exhibitions for the visually-impaired: a universal present framework beyond the museum - Seow, Bernice Jia Yun (Nanyang Technological University, 2022)
This thesis posits that inclusivity for the visually-impaired is necessary in all arts and cultural spaces regardless of whether they are museums or galleries. It acknowledges that while museums have been actively trying to include accessibility programmes and features, smaller-scale exhibitions curated by independent curators, project managers and private galleries have not done enough to include the visually-impaired. This thesis begins by first examining the definitions and treatment of disability and visualimpairment in Singapore before considering some international and local case-studies on art and accessibility programmes for the visually-impaired. The discussion is grounded in both traditional and recent models in the field of disability studies: the Medical, Social and Transculturalized Diversity and Inclusion Models; and psychosociological theories such as the Actor-Network Theory and the process of resilience. Through an analysis of case-studies and the application of the above theoretical models, this thesis proposes a framework of considering the universal present – the current disadvantages that the visually-impaired face at exhibitions and how to overcome them - to guide curators and project managers in carrying out accessible events in small-scale exhibitions and private shows.